2020
DOI: 10.1097/md.0000000000022113
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ropivacaine plus sufentanil and ropivacaine plus dexmedetomidine for labor epidural analgesia

Abstract: Objective: Effective analgesia during delivery can not only decrease pain, but also have a significant function in ensuring the safety of baby and mother. Sufentanil is generally used opioid with ropivacaine in epidural anesthesia in labor pain management; however it can cause some adverse reaction. Dexmedetomidine is an a2-adrenoceptor agonist with high selectivity. It possesses opioid-sparing and analgesic effects and it is suitable for the long-term and short-term intraoperative sedation. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…It is suggested that the whole-labor MMA regimen has no adverse effects on the newborn and is safe. To analyze the reasons, the drugs ropivacaine and sufentanil used in PCEA in this study hardly pass the placental barrier, have no inhibition on neonatal breathing, and do not affect the uteroplacental blood circulation [ 20 , 21 ]. And when it is combined with auricular acupoint pressing, TENS, and acupoint injection during the incubation period, it not only gives full play to the sedative and analgesic effects of multiple-acupoint stimulation to ensure full analgesia during labor but also fully ensures the safety of the newborn.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the whole-labor MMA regimen has no adverse effects on the newborn and is safe. To analyze the reasons, the drugs ropivacaine and sufentanil used in PCEA in this study hardly pass the placental barrier, have no inhibition on neonatal breathing, and do not affect the uteroplacental blood circulation [ 20 , 21 ]. And when it is combined with auricular acupoint pressing, TENS, and acupoint injection during the incubation period, it not only gives full play to the sedative and analgesic effects of multiple-acupoint stimulation to ensure full analgesia during labor but also fully ensures the safety of the newborn.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine (Dex) is a highly selective α 2-adrenergic receptor agonist, which can act directly on peripheral α 2 receptors, reduce the release of norepinephrine, and further show sedative and analgesic effects [ 16 ]. Chen et al [ 17 ] applied Dex combined with ropivacaine in parturition analgesia successfully with excellent application effects.…”
Section: Introductionmentioning
confidence: 99%
“…7 A prior study found that epidural administration of 0.08% ropivacaine + 0.5 μg/mL DEX had the optimal effect, with high maternal satisfaction. 8 Similarly, another study also reported that when DEX was combined with 0.1% ropivacaine, 0.5 μg/mL was the appropriate concentration of DEX for epidural labor analgesia. 9 In the present study, we observed more parturients with Bromage scores of ≥2 in the S0.3 group than in the remaining 3 groups when the VAS score was maintained between 0 and 3 throughout labor (P < .05).…”
Section: Discussionmentioning
confidence: 94%